Code Obfuscation: A Comprehensive Approach to Detection, Classification, and Ethical Challenges - Tomer Raitsis; Yossi Elgazari; Guy E. Toibin; Yotam Lurie; Shlomo Mark; Oded Margalit (Algorithms)
Code obfuscation has become an essential practice in modern software development, designed to make source or machine code challenging for both humans and computers to comprehend. It plays a crucial role in cybersecurity by protecting intellectual property, safeguarding trade secrets, and preventing unauthorized access or reverse engineering. However, the lack of transparency in obfuscated code raises significant ethical concerns, including the potential for harmful or unethical uses such as hidden data collection, malicious features, back doors, and concealed vulnerabilities. These issues highlight the need for a balanced approach that ensures the protection of developers’ intellectual property while addressing ethical responsibilities related to user privacy, transparency, and societal impact. This paper investigates various code obfuscation techniques, their benefits, challenges, and practical applications, underscoring their relevance in contemporary software development. This study examines obfuscation methods and tools, evaluates machine learning models—including Random Forest, Gradient Boosting, and Support Vector Machine—and presents experimental results aimed at classifying obfuscated versus non-obfuscated files. Our findings demonstrate that these models achieve high accuracy in identifying obfuscation methods employed by tools such as Jlaive, Oxyry, PyObfuscate, Pyarmor, and py-obfuscator. This research also addresses emerging ethical concerns and proposes guidelines for a balanced, responsible approach to code obfuscation.